(untitled) (Mustansiria Dental Journal, 2024)
Introduction: The accurate assessment of skeletal maturation and residual growth is critically important in orthodontics, especially in insulin-dependent diabetes mellitus growing subjects in which the available data on their growth are conflicting and are mainly derived from cross-sectional studies. Aim of the study: This study aimed to examine the association between the calcification stages of the second mandibular molar, the maturation of the middle finger phalanx, and the chronological age of the patients. Material and Methods: The sample consisted of 80 Iraqi subjects of Type1 Diabetic Mellitus (T1DM), 40 males and 40 females. For each subject, two per apical radiographic were used, one for the mandibular right second molar and the other for the middle phalanx of the middle finger (MP3). Demirjian method (1973) was assessed for the ossification of teeth, while Staging of the Middle phalanx of the third finger radiographs was done according to the Rajagopal and Kansal method. Result: The results showed no significant association between skeletal and dental maturity for both genders in T1DM growing subjects and a negative association can be seen between dental age and skeletal age in total, male and female T1DM subjects. Conclusion: mandibular second molar calcification stages of Demirgian’s classification are unreliable as a skeletal maturity indicator in TIDM.